PENINGKATAN PRODUKTMTAS PENCIPTAAN CERPEN JAWA MELALUI PENDEKATAN PROSES - Suwardi Suwardi (Jurnal Cakrawala Pendidikan, 1998)
Failures in the teaching of Javanese short story writingare in general induced by the mistake of adopting the approachthat is oriented more to the product rather than to the process.Consequently, pupils are reluctant to go through a creativeprocess and frequently lured to take short cuts by both imitatingand plagiarizing somebody else's work.The aforen~entioned reality could be prevented byapplying a creative process approach in producing Javaneseshort stories. This approach illvolves four stages, i.e., (1) thepreparation stage, namcly, that of raising an idea derived fromone's life experiences and from increases reading, (2) theincubation stage, nainely, that of the maturation of an idea, hypracticing contemplation of experiences and observatio~~s(3, )the illuinination stage, namely, that of expressing the idea, and(4) the verification stage, namely, that or stimulating andmotivating pupils' activities through comparison of their ownworks and those of their collectives.The steps to be taken by the teacher in applying theprocess approach are, (1) retelling high-quality Javanese shsortstories, (2) retelling thcm from different poi~its of view, (3)reteling them from incomplete original by adding imaginedparts, (4) stimulating pupils' creativily by offering a variety oft hen~es.